ANALISIS BUDAYA ORGANISASI PADA INDUSTRI DISTRIBUSI DAGANG PRODUK KESELAMATAN (STUDI KASUS PADA PT XYZ) - Arthamevia, Athirah Delfi; Febriantina, Susan; Maulida, Ervina (ANALISIS, 2025)
This study aims to analyze the organizational culture applied at PT XYZ, a company engaged in the trading of safety, abrasive, tools, and coatings products as an official distributor. The approach used is qualitative with data collection techniques through in-depth interviews with five participants from different work units, as well as field observations. The results of the study indicate that the organizational culture at PT XYZ is built on the values of hard work, honesty, and team cohesion. The implementation of this culture is evident in daily work habits, interactions between employees, and a family-based work system. Challenges in maintaining a conducive organizational culture include the impact of exchange rate fluctuations on company operations and the risk of value inconsistency when there is a deviation in attitude or lack of openness. However, organizational culture can still be maintained through informal collaboration and an adaptive management approach. This study is expected to contribute to the development of organizational culture theory and become a practical reference for similar companies in forming a strong work culture that is resilient to external challenges